HPV vaccine confidence and cases of mass psychogenic illness following immunization in Carmen de Bolivar, Colombia. Issue 1 (2nd January 2019) - Simas, Clarissa; Munoz, Nubia; Arregoces, Leonardo; Larson, Heidi J.
ABSTRACT: We report the case of multiple adverse reactions following HPV vaccination in Colombian adolescents in Carmen de Bolivar. In August 2012, the country introduced a school-based HPV immunization programme which successfully reached over 90% of the target population in the first year. In 2014, between May 29th and June 2nd, 15 adolescent girls in one school presented adverse reactions after vaccination and were admitted to the local hospital. Soon, videos of girls fainting, twitching, and arriving unconscious at emergency rooms started to appear in national news media as well as on social media platforms such as YouTube. The viral spread of these videos and disturbing images were followed by the viral spread of symptoms, with over 600 cases reported across Colombia. Thorough epidemiological investigation by Colombian health authorities found no organic association between the teenagers' symptoms and the HPV vaccine, concluding this was a case of mass psychogenic reaction to vaccination. Scientific evidence did not appease the anxious public whose confidence in HPV immunization dropped dramatically. By 2016, HPV vaccine uptake among eligible girls declined to 14% for the first dose and 5% for the complete course, down from 98% and 88%, respectively, in 2012. We document this case and discuss the role of news and social media, particularly YouTube, as a driver of contagious psychogenic reactions. We also discuss the role of health authorities and government, and the importance of acting rapidly and appropriately to contain the spread of such symptoms and maintain public confidence in vaccines.